The cryopolitics of reproduction on ice : a new Scandinavian ice age - Kroløkke, Charlotte; Petersen, Thomas Søbirk; Herrmann, Janne Rothmar; Bach, Anna Sofie; Adrian, Stine Willum; Hansen, Rune Klingenberg; Petersen, Michael Nebeling (Emerald studies in reproduction, culture and society., 2019)
Reproduction has entered a new ice age: the ability to cryopreserve reproductive cells, tissue and embryos are fundamentally changing our understanding of what it means to be a reproductive citizen. This book explores the ways in which visions of desirable reproductive futures entangle with advances in freezing technologies, with the authors situating their discussions of cryo-fertility within the Scandinavian region, asking:How does cryopreservation help mobilize particular understandings of reproductive time, reproductive rights and reproductive autonomy? What values are embedded within Scandinavian laws that seek to regulate cryo-technologies? How are frozen states enacted in clinical settings and how do the women and men who freeze imagine the preservation of reproductive parts?These questions demand a collaborative approach. The authors empirically cut across the arenas of bioethics/law, practices/experiences, and culture/commerce in order to pin down often complex and far-reaching answers.